Evaluación de los afluentes que ingresa a la Laguna de Yahuarcocha, Provincia de Imbabura - Lucio León, Melany Yulieth (2022)
The Yahuarcocha lagoon is a natural wonder and one of the most important tourist centers of Ecuador, in this sense around it are carried out a number of human activities (agriculture, livestock, trade, among others.), These anthropogenic activities are a focus of pollution, causing a problem of deterioration for the lake system, because the wastewater have as final destination the body of water of the lagoon. Taking into account the above mentioned, the general objective of this research is to evaluate the tributaries that enter the Yahuarcocha lagoon, using analytical techniques to determine the pollutant load that enters this body of water. To achieve the objective of the research, the following methods were used: deductive, inductive and experimental, complemented with physicochemical and microbiological techniques, which allowed us to obtain data to contrast between each of the tributaries that enter the lagoon. In this way, the following conclusions were reached: Six water inflows to the Yahuarcocha lagoon were identified, among which are the tributary near the Aduana, the San Antonio ditch, Manzana Huayco stream, the PTAR tributary, the Polo Golo stream and the El Quince - Rio Tahuando stream. Regarding the need to determine the status of the tributaries that enter the lagoon, the tributary near the customs house has a poor water quality index with a value of 48.853, while the others are in a regular index, with a range of 51.82 to 57.90. Once the pollutant load was calculated, it was determined that the 'San Antonio' irrigation ditch is the most polluting of phosphates 0.013 mg/s and the 'Manzano Huayco' stream of total nitrogen 0. 0249 mg/s of the six tributaries, although this is one of those that contain a lower concentration of pollutants (nitrates, nitrites, phosphates, oil and grease, etc.), but it contributes a greater amount of pollutants to the body of water of the Yahuarcocha lagoon, accelerating the process of eutrophication and can transform the lagoon into a swampy area and then become firm ground.